Sons and Lovers - Lawrence, D. H (London Penguin Books, 1995)
Sons and Lovers' tells the story of Paul Morel, a young man and budding artist. The refined daughter of an old family, Gertrude Coppard, meets a rough-hewn miner at a Christmas dance and falls into a whirlwind romance. But soon after her marriage to Walter Morel, she realizes the difficulties of living off his meager salary in a rented house. The couple fight and drift apart and Walter retreats to the pub after work each day. Gradually, Mrs. Morel's affections shift to her sons.
Keywords: Working class families -- Young men -- England